Public policies focused on the prevention and protection of early childhood in Peru - Moreno Zavaleta, María Teresa (2022)
The implementation of public policies for risk prevention and protection of early childhood continues to be a major challenge for Latin American countries. Although there are international and national regulatory frameworks, policies require articulated multisectoral management with a holistic approach, focusing on developing competencies in those involved in child development: family, school, and community. This process also involves a paradigm shift, banishing the needs-based approach and assuming the human rights-based approach from the perspective of diverse childhoods. The existing regulatory frameworks are still discursive, not operational enough, and disjointed at the different levels of government. This research analyzes the international and national efforts that allowed public policy implementation and reveals how much is being done and how little progress is being made to achieve short and medium-term results that will benefit early childhood.